Tutorless board game as an alternative to tabletop exercise for disaster response training : perception of interaction engagement and behavioral intention - Chew, Keng Sheng; Shirly Wong Siew, Ling; Izzah Safah, Tarazi; Janet Weilly, Koh; Nor Azeriyatul ‘Ain, Ridzuan; Syed Azrai Shah, Wan Allam (BioMed Central Ltd, 2023)
Background Although tabletop exercise is a commonly used method for disaster response training, it is laborintensive, requires a tutor for facilitation and may not be ideal in a pandemic situation. Board game is a low-cost and portable alternative that can be utilized for this purpose. The purpose of this study was to compare the perception of interaction engagement and behavioral intention to use a newly developed board game with tabletop exercise for disaster training. Methods Using the Mechanics-Dynamics-Aesthetics’ (MDA) framework, a new, tutorless educational board game known as the Simulated Disaster Management And Response Triage training (“SMARTriage”) was frst developed for disaster response training. Subsequently, the perceptions of 113 fnal year medical students on the “SMARTriage” board game was compared with that of tabletop exercise using a crossover design. Results Using Wilcoxon signed rank test, it was that found that tabletop exercise was generally rated signifcantly higher (with p<0.05) in terms of perceived usefulness, perceived ease of use and behavioral intention compared to tutorless “SMARTriage” board game. However, in terms of attitude and interaction engagement, there was no signif‑ cant diference between these two learning methods for most of the items. Conclusion Although a clear preference for tutorless board game was not demonstrated, this study suggests that board game was not inferior to tabletop exercise in fostering interaction engagement suggesting that “SMARTriage” board game could potentially be used as an adjunct for teaching and learning activities